(untitled) (International Conference on Computers in Education, 2013)
The purpose of this study was to develop automatic keyword, three-layer concept map, and scoring for supporting and measuring college students ’ summaries in reading academic texts. The three layers represent: (1) the central idea of a text, (2) the main idea of each paragraph, and (3) the supporting ideas of each paragraph . A sample of 52 college students who study English as a Foreign Language (EFL) was grouped into the experimental and control groups, 28 and 24 students in each. The result s of this study indicate that the students of the experimental group made more significant improvement on reading comprehension and summarization after receiving the explicit and strategic feedback of automatic keywords, three-layer concept maps, and scores than students in the control group. The automatic keywords, three-layer concept maps and scores not only become reliable predictors to evaluate the students’ summarization but also serve as scaffolds to improve their reading comprehension and summarizati on as they actively engage in self-regulated learning.